CLINICAL-MORPHOLOGIC AND MOLECULAR-BIOLOGIC PROGNOSTIC FACTORS FOR RARE FORMS OF UTERINE CANCER - K. P. Laktionov; G. M. Abdullayeva; O. A. Anurova (ABV-press, 2014)
This review of literature is devoted to rare forms of uterine cancer. Comparative characteristics of each histological type are given. Clinical-morphologic and molecular-biologic prognostic factors are analyzed in details.